Did Merkel's 2015 decision attract more migration to Germany? - Jasper Tjaden; Tobias Heidland (European Journal of Political Research, 2024)
In 2015, German Chancellor Angela Merkel decided to allow over a million asylum seekers to cross the border into Germany. One key concern was that her decision would signal an open-door policy to aspiring migrants worldwide – thus further increasing migration to Germany and making the country permanently more attractive to irregular and humanitarian migrants. This `pull-effect' hypothesis has been a mainstay of policy discussions ever since. With the continued global rise in forced displacement, not appearing welcoming to migrants has become a guiding principle for the asylum policy of many large receiving countries. In this article, we exploit the unique case study that Merkel's 2015 decision provides for answering the fundamental question of whether welcoming migration policies have sustained effects on migration towards destination countries. We analyze an extensive range of data on migration inflows, migration aspirations and online search interest between 2000 and 2020. The results reject the `pull effect' hypothesis while reaffirming states' capacity to adapt to changing contexts and regulate migration.
Keywords: 330; migration; policy; refugee; pull effect; Germany